2023
DOI: 10.1186/s13052-023-01422-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in healthy Italian school-age children: a single-center cross-sectional study

Abstract: Background Vitamin D is involved in calcium homeostasis and bone metabolism, although its extra-skeletal actions are also well-known. Low serum 25(OH)D levels are common both in adults and children worldwide. Methods The purpose of this cross-sectional study was to determine the distribution of 25(OH)D levels in a cohort of healthy Italian school-age children, aged 5–10 years, in relationship to determinants of vitamin D deficiency such as season, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Therefore, it is more prevalent in high-latitude countries where sunlight incidence angles are narrow, in urban areas characterized by high-rise buildings and air pollution, and during the winter and spring seasons when sunlight exposure is reduced. [12,13,21,22,[24][25][26] Yeşiltepe-Mutlu G et al reported in their study that vitamin D deficiency was most common in the Black Sea region due to its cloudy and rainy weather, particularly in the spring and winter seasons, and least typical in the Aegean region with abundant sunshine, especially during the summer season. [15] Additionally, a study conducted on adults in Bursa noted that the prevalence of 25(OH)D levels <20 ng/mL was highest from March to May and lowest from September to November.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is more prevalent in high-latitude countries where sunlight incidence angles are narrow, in urban areas characterized by high-rise buildings and air pollution, and during the winter and spring seasons when sunlight exposure is reduced. [12,13,21,22,[24][25][26] Yeşiltepe-Mutlu G et al reported in their study that vitamin D deficiency was most common in the Black Sea region due to its cloudy and rainy weather, particularly in the spring and winter seasons, and least typical in the Aegean region with abundant sunshine, especially during the summer season. [15] Additionally, a study conducted on adults in Bursa noted that the prevalence of 25(OH)D levels <20 ng/mL was highest from March to May and lowest from September to November.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, a number of agencies—the German Nutrition Society, the Dutch Health Ministry, the Nordic Council of Ministers (NORDEN), the UK Scientific Advisory Committee on Nutrition (SACN), the European Food Safety Authority (EFSA), and the European Society for Paediatric Gastroenterology Hepatology and Nutrition (ESPGHAN)—revised the definition of Vit D status, proposing different cut-off levels for sufficiency (>20 ng/mL or ≥30 ng/mL), insufficiency (10–20 ng/mL or 20–30 ng/mL), deficiency (10–20 ng/mL or <10 ng/mL), and severe deficiency (<10 ng/mL or <5 ng/mL) [ 7 ]. Several studies have associated maternal Vit D deficiency (VDD) with undesirable effects during pregnancy, impacting both the mother [ 8 , 9 , 10 , 11 ] and the newborn [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The seasonal variations of solar radiation reaching the earth's surface are reflected in the amount of electromagnetic energy that reaches the exposed skin of humans, thus resulting in the serum 25(OH)D level seasonal pattern, with a maximum peak in summer and a minimum in spring [8,9]. Although the seasonal variations of vitamin D levels have been known for a long time, in-depth studies investigating sex-and age-related variations are mainly limited to relatively small cohorts [10].…”
Section: Introductionmentioning
confidence: 99%